The Role of CSR in Enhancing ESG Impact: Case Study of The Pengembangan Petani Madu Sari Alam Semberah (TAMU SARAH) Program - Joshi, Luthfi Kurniawan; Yustriawan, Reza Bagus (Global Writing Academica Researching and Publishing, 2024)
In the last decade, the principles of ESG (Environmental, Social, and Governance) have become not just a trend but a business paradigm for companies. This aligns with the increasing praxis of the ‘S’ or social aspect in ESG, which companies implement through CSR programs. This study, employing a qualitative approach through a single case study type, specifically highlights the Pengembangan Petani Madu Sari Alam Semberah (TAMU SARAH) CSR Program conducted by PT Pertamina EP Sangatta-Semberah Field. The findings of this study indicate that the CSR program praxis is relevant to the company’s ESG principles, which can be measured through, first, community engagement in community development praxis. This praxis has strengthened the relationship between the company and the local community. The second is local content. Through the CSR program, the company not only creates group satisfaction with the ongoing program but also tends to contribute to the pleasure and happiness of group members. The last one is the indirect economic impact. Through ECON-ESG measurements, it was found that the Pengembangan Petani Madu Sari Alam Semberah (TAMU SARAH) CSR program does not lead to a decrease in GDP; on the contrary, it positively contributes to macroeconomic conditions.